Postoperative Sedation Duration as an Independent Risk Factor for Postoperative Pneumonia in Head and Neck Cancer Patients Undergoing Free Flap Reconstruction. (1st March 2022) - Chuang, Chih-Chao; Chen, Mei-Chun; Perng, Cherng-Kang; Liao, Wen-Chieh; Wang, Tien-Shiang; Wu, Szu-Hsien; Shih, Yu-Chung; Lin, Chih-Hsun; Hsiao, Fu-Yin; Feng, Chin-Jung; Ma, Hsu
Abstract : Objective: Patients who had reconstruction for head and neck cancer usually have long duration of postoperative sedation and intensive care. This is due to the complex nature of large-area soft tissue defect surgeries and upper respiratory tract infections associated with them. Postoperative pulmonary complications are common in these patients. In this study, we analyzed the risk factors and the relationship between postoperative complications and the duration of sedation to improve the patients' recovery process after free flap reconstruction for head and neck surgery. Materials and Methods: This was a retrospective study that included 188 patients who had head and neck surgery with free flap reconstruction in 2011 (traditional recovery group) and 2018 (early recovery group). Postoperative recovery events were compared between the 2 groups. Complications such as pneumonia, wound infection, vascular thrombosis, and bleeding were also analyzed. Results: The results showed that the early recovery group had a shorter duration of sedation ( P < 0.001), shorter duration of intensive care unit stay ( P = 0.05), more rapid ventilator weaning ( P < 0.001), and fewer pneumonia events (8.8% vs 39.1%) than the traditional recovery group. Wound- and vessel-related complications were not affected by the duration of sedation. Conclusions: Our study demonstrated that shortening the duration of postoperative sedation can effectively decrease the length of intensive care unit stay and reduce postoperative incidence of pneumonia without increasing wound- and vessel-related complications.